Understanding the role of topography and air-mass mixing across the Dinaric Alps using stable isotope measurements - Sanchez Ortiz, Gabriela, author; Rugenstein, Jeremy Caves, advisor; Gallen, Sean, committee member; Keys, Patrick, committee member (Colorado State University. Libraries, 2024)
The collision of Eurasia with the Adria microplate within the Alpine-Himalayan orogenic belt resulted in the formation of the Dinaric Alps and the creation of basins that later evolved into the Dinaride Lake System (DLS). The topography of the Dinaric Alps during this period of formation remains poorly understood, contributing uncertainties about the geodynamic processes that shaped the range and the climatic conditions that supported the highly diverse DLS. The oxygen isotope composition (δ18O) of authigenic carbonates can be used as a paleo-altimeter to reconstruct past elevations of mountain ranges. However, changes in factors such as temperature and moisture sources can affect the composition of the waters that form these authigenic minerals. In an effort to constrain the Miocene δ18O pattern across the Dinaric Alps, we collected new stream and carbonate samples from seven basins ranging from the coast of Croatia to high-elevation basins in Bosnia and Herzegovina. In addition, we compiled published water samples to better constrain the modern δ18O pattern of the Dinaric Alps. Today, we find higher δ18O at the coast and lower δ18O near the crest of the modern range. We observe a different trend in the lacustrine carbonate δ18O; the highest Miocene δ18O values are near the crest of the range, with lower δ18O values at the coast. We attribute the modern δ18O pattern to the orographic uplift of air parcels containing moisture from the Mediterranean Sea. The Miocene-age δ18O pattern obtained from the lacustrine carbonates is likely a result of the evaporation of the lake waters that formed the carbonates at the crest of the range. Using these high δ18O values can lead to the underestimation of the Miocene topography of the Dinaric Alps, thus there is a need for a novel method to eliminate the effect of evaporation on lacustrine carbonates.
Keywords: Croatia; Miocene; Bosnia and Herzegovina; paleoaltimetry; Dinaric Alps